Somatic cell count obtained by ekomilk scan® and correlations with other methods of analysis - Gonçalves, Ana Carolina Siqueira [UNESP]; Roma Júnior, Luiz Carlos; Privatti, Rafaela Torrezan; Salles, Márcia Saladini Vieira; De Paz, Claudia Cristina Paro; Zadra, Lenira El Faro; Vidal, Ana Maria Centola (FapUNIFESP (SciELO), 2018)
The study aimed to evaluate the equipment Ekomilk Scan® as an alternative to somatic cell count (SCC) in milk. For this individual cow milk samples of various ages and different stages of lactation in northeastern state of São Paulo region were collected. The analyzes performed were divided into variables related to the equipment: repeatability and reproducibility, and variables that could influencing the results as: use of preservatives, temperature, time between collection and analysis, breed and milk composition, besides analysis to relate the Ekomilk Scan® with the standard method-direct microscopy and reference-flow cytometry. As the result, for samples analysis, it shouldn’t be added preservative and these should be conducted on the same day of collection; however, temperature sample did not significantly influence results. Furthermore, Ekomilk Scan® did not show good correlation of results with the method of direct microscopy; however, it was necessary to generate equations for a positive correlation between flow cytometry and Ekomilk Scan®. Therefore, it is concluded that the equipment tested is not accurate but it can be an alternative for SCC monitoring in productive units since it uses calibration equations of results.
Contagem de células somáticas obtidas pelo equipamento Ekomilk Scan® e suas correlações com outros métodos de análise
Keywords: Alternative method; Monitoring; Somatic cell count; Udder health